2021
DOI: 10.1101/2021.09.29.462128
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell RNA-seq analysis reveals aberrant CSF1 expression in disease-causing synovial fibroblasts of pigmented villonodular synovitis

Abstract: Objectives: Although the role of the CSF1/CSF1R axis in pigmented villous synovitis (PVNS) has been confirmed, the cells that express CSF1 and CSF1R and the underlying mechanism remain unclear. Single-cell RNA sequencing (scRNA-seq) of PVNS obtained through biopsies depicted the cellular diversity of PVNS, revealed specific CSF1/CSF1R-expressing cells and further identified novel gene expression that is associated with the development of PVNS. Methods: scRNA-seq was performed on tissues obtained from the 6 bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…RNA-seq led to the reclassification of four “ HMGA2::NCOR2 giant cell tumors”. The transcriptional similarities between the CSF1 transcripts and newly identified transcripts suggest an analogous oncogenic activation pathway ( 28 ), illustrated by the efficacy of CSF1 inhibitors in both situations.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq led to the reclassification of four “ HMGA2::NCOR2 giant cell tumors”. The transcriptional similarities between the CSF1 transcripts and newly identified transcripts suggest an analogous oncogenic activation pathway ( 28 ), illustrated by the efficacy of CSF1 inhibitors in both situations.…”
Section: Discussionmentioning
confidence: 99%
“…Considering as an essential source of CSF1, we inferred that fibroblasts may be recognized by CSF1R that mainly expressed on the macrophages, thus subsequently recruiting the macrophages. Fibroblast-macrophage interaction that centers around the CSF1-CSF1R signaling axis has already been proved essential in the occurrence and progression of various cancers [ 33 , 34 ]. Moreover, Qi et al found that FAP + CAFs and SPP1 + (secreted phosphoprotein 1) macrophages interacted with each other through chemerin, TGF-β, and IL-1, accompanied by stimulating the formation of immune-excluded desmoplastic structure and limiting the T cell infiltration [ 35 ].…”
Section: Discussionmentioning
confidence: 99%